An improved simplified rules Fuzzy Logic Speed Controller method applied for induction motor drive. (October 2020) - Talib, M.H.N.; Ibrahim, Z.; Abd. Rahim, N.; Zulhani, R.; Nordin, N.; Farah, Nabil; Razali, A.M.
Abstract: Fuzzy Logic Speed Controller (FLSC) has been widely used for motor drive due to its robustness and its non-reliance to real plant parameters. However, it is computationally expensive to be implemented in real-time and prone to the fuzzy rules' selection error which results in the failure of the drive's system. This paper proposes an improved simplified rules method for Fuzzy Logic Speed Controller (FLSC) based on the significant crisp output calculations to address these issues. A systematic procedure for the fuzzy rules reduction process is first described. Then, a comprehensive evaluation of the activated crisp output data is presented to determine the fuzzy dominant rules. Based on the proposed method, the number of rules was significantly reduced by 72%. The simplified FLSC rule is tested on the Induction Motor (IM) drives system in which the real-time implementation was carried out in the dSPACE DS1103 controller environment. The simulation and experimental results based on the proposed FLSC have proved the workability of the simplified rules without degrading the motor performance. Highlights: The systematic simplification procedure is proposed by fuzzy rules selection method based on the significant crisp output control calculation. The proposed method fulfills the fuzzy properties of completeness, consistency and continuity to ensure workability of the system in wide speed range operation for four quadrant operation. The simplified method is beneficial to minimize the computation time, simplicity and low cost implementation which is suitable for a high performance drive application. The experiment results validate the simulation results based on the proposed simplified rules without degrading the performance. The proposed method is applicable for any plant or machine and does not require knowledge of the plant or machine parameters.